Zambia : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria, and Financing Assurances Review. (IMF Staff Country Reports; Country Report, 2010)
Zambia showed strong economic performance with robust growth and moderating inflation under the Extended Credit Facility (ECF). It showed sound macroeconomic policies and progress in structural reforms. The Zambian authorities consider their main challenge to create fiscal space for priority spending, enhance economic diversification, and reduce poverty. The strengthening of debt management and project appraisal capacity are critical in this regard. To meet the financing needs for addressing growth-critical infrastructural requirements, the Zambian authorities requested a waiver for the nonobservance of a performance criterion on nonconcessional external debt.